2021
DOI: 10.1136/gutjnl-2021-325181
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, double-blind diagnostic multicentre study of confocal laser endomicroscopy for wheat sensitivity in patients with irritable bowel syndrome

Abstract: ObjectiveA considerable proportion of patients with irritable bowel syndrome (IBS) may be wheat-sensitive and respond to a gluten-free diet (GFD) although they do not have coeliac disease. However, a diagnostic test for wheat sensitivity (WS) is missing. Our study evaluated the diagnostic accuracy (sensitivity and specificity) of confocal laser endomicroscopy (CLE) for the identification of WS as primary outcome.DesignIn this prospective, double-blind diagnostic study 147 non-coeliac patients fulfilling the Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…Third, specific immune reactions to food antigen exposure might better identify problem foods. Gutspecific reactions have been demonstrated in patients with foodrelated symptoms by the demonstration of IgE and mast cell activation associated with intramucosal injection of food antigens (64) and by the direct observations of injury response using confocal laser endomicroscopy after topical application of specific food antigens to the duodenum and an intramucosal injection of antigens during colonoscopy (67)(68)(69)(70). Both methods have provided evidence that dietary restriction of implicated antigens led to clinical benefits for patients.…”
Section: Diets Targeting Specific Food Types or Componentsmentioning
confidence: 99%
“…Third, specific immune reactions to food antigen exposure might better identify problem foods. Gutspecific reactions have been demonstrated in patients with foodrelated symptoms by the demonstration of IgE and mast cell activation associated with intramucosal injection of food antigens (64) and by the direct observations of injury response using confocal laser endomicroscopy after topical application of specific food antigens to the duodenum and an intramucosal injection of antigens during colonoscopy (67)(68)(69)(70). Both methods have provided evidence that dietary restriction of implicated antigens led to clinical benefits for patients.…”
Section: Diets Targeting Specific Food Types or Componentsmentioning
confidence: 99%
“…Direct imaging of fluorescent tracers was used to address barrier function in live epithelia and mucosae, but provides limited spatiotemporal resolution as there is little or no retention in target areas/structures. 21,43,44 By using the sandwich assay, an endpoint leak detection assay, previous work in our lab had already suggested that macromolecule passage in epithelia is rather rare across epithelial layers. 23 As a matter of fact, globally assessed permeability does not allow on to safely conclude about the underlying mechanisms since passage can, by way of example, be located to specific subareas of the layer only.…”
Section: Discussionmentioning
confidence: 99%
“…Recent emerging evidence indicates a role for food-induced mucosal alterations in the pathogenesis of upper GI alterations and symptoms. A number of studies used confocal laser endomicroscopy to demonstrate duodenal mucosal reactions to food allergens in patients reported to have IBS (69)(70)(71)(72). In a preliminary report, improvement of symptoms and duodenal barrier function was observed after 6 weeks of a low FODMAP diet in FD (73).…”
Section: Gi-specific Immune Activation or Intolerancesmentioning
confidence: 99%
“…A likely prerequisite for duodenal reactions to mucosally applied nutrients is increased mucosal permeability (77,78). In both the confocal laser endomicroscopy and in the 6 food elimination diet studies, similar to the IBS studies, patients were negative on blood tests for classical immunoglobulin E (IgE)-mediated food allergies (69–72,75,76). One hypothesis is local production of food-targeting IgEs (79), but to date there are no reports that have evaluated this possibility in the upper GI tract.…”
Section: Allergic and Immune Mechanismsmentioning
confidence: 99%